The consideration of processes non-stationarity in gas tract of the internal combustion engine - L. V. Plotnikov; B. P. Zhilkin; Y. M. Brodov (Известия высших учебных заведений: Проблемы энергетики)
The results of an experimental study of the effect of the gas-dynamic non-stationarity on gas dynamics and the local heat in the exhaust pipe of a piston engine are presented in the article. Two types of resolution of the gas-dynamic non-stationarity exist for exhaust process in internal combustion engines. Thermomechanical non-stationarity is observed for exhaust process in engines. Thermomechanical non-stationarity influence both on the gas-dynamic, and the heat exchange flow parameters. The coefficient of heat transfer mobility takes into account thermo-mechanical non-stationarity when calculating local heat transfer coefficient.